2017
DOI: 10.1111/ijac.12810
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion synthesis, optical and photocatalytic properties of vanadium‐doped nano ZnO

Abstract: In the present work, vanadium-doped ZnO nanoparticles with different V concentrations were prepared via microemulsion method and employed as an effective photocatalyst for the degradation of methylene blue. The prepared samples were characterized by different techniques such as thermogravimetric and differential thermal analysis (TG-DTA), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), X-ray diffraction (XRD), scanning electron microscopy (SEM), elemental mapping (MAP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Optical investigations show the creation of local energy states after doping, and photocatalytic activity augmentation can be explained by localized-state charge trapping, increased surface area, and porosity [37]. Studies regarding the effect of transition metal doping on the photoelectrochemical properties of metal oxide films have been widely available in literature, some of which indicate that vanadium (V) doping improves the UV sensibility and photoresponse of ZnO, TiO 2 , and α-Fe 2 O 3 metal oxides by increasing the rate of visible light absorption, leading to increased photocatalytic activity [38][39][40][41][42]. Photocatalytic degradation studies of organic dyes [43][44][45] and synthesis/characterization studies of vanadium doped ZnO nanostructures [46][47][48] have been reported, however there is a gap about a comparative study regarding the influence of various oxidation states of vanadium.…”
Section: Introductionmentioning
confidence: 99%
“…Optical investigations show the creation of local energy states after doping, and photocatalytic activity augmentation can be explained by localized-state charge trapping, increased surface area, and porosity [37]. Studies regarding the effect of transition metal doping on the photoelectrochemical properties of metal oxide films have been widely available in literature, some of which indicate that vanadium (V) doping improves the UV sensibility and photoresponse of ZnO, TiO 2 , and α-Fe 2 O 3 metal oxides by increasing the rate of visible light absorption, leading to increased photocatalytic activity [38][39][40][41][42]. Photocatalytic degradation studies of organic dyes [43][44][45] and synthesis/characterization studies of vanadium doped ZnO nanostructures [46][47][48] have been reported, however there is a gap about a comparative study regarding the influence of various oxidation states of vanadium.…”
Section: Introductionmentioning
confidence: 99%